Կաթողիկոսասարի մոռացված վանքը - Կարապետյան, Բակուր; ՍարգսյաՆ, Գագիկ Մ. (ՀՀ ԳԱԱ հրատ.)
В относящихся к историческому Арцаху первоисточниках и исследованиях неоднократно упоминается знаменитый Католикосасарский монастырь, как место летнего пребывания католикоса и как резиденция католикосов. Говорится, что монастырь находится в долине реки Тартар, но его точное местоположение неизвестно. In the original sources relating to the Historic Artsakh and in scholarly historiographic literature multiple mentions have been made of the notable Monastery of the Katholicos Mountainas a summer house of the Albania’s Katholicoses, as well as the Monastery Seat of Katholicos.It is indicated that it was in the Valley of Tartar, but its precise spot is unknown.
Keywords: Հայագիտություն; Պատմություն